Safety Studies for Use of Adipose Tissue‐Derived Mesenchymal Stromal/Stem Cells in a Rabbit Model for Osteoarthritis to Support a Phase I Clinical Trial. (26th October 2016) - Riester, Scott M.; Denbeigh, Janet M.; Lin, Yang; Jones, Dakota L.; de Mooij, Tristan; Lewallen, Eric A.; Nie, Hai; Paradise, Christopher R.; Radel, Darcie J.; Dudakovic, Amel; Camilleri, Emily T.; Larson, Dirk R.; et al.
Abstract: Adipose‐derived mesenchymal stem cells (AMSCs) offer potential as a therapeutic option for clinical applications in musculoskeletal regenerative medicine because of their immunomodulatory functions and capacity for trilineage differentiation. In preparation for a phase I clinical trial using AMSCs to treat patients with osteoarthritis, we carried out preclinical studies to assess the safety of human AMSCs within the intra‐articular joint space. Culture‐expanded human AMSCs grown in human platelet‐lysate were delivered via intra‐articular injections into normal healthy rabbit knees and knees at risk for the development of osteoarthritis after bilateral medial anterior hemimeniscectomy. Treatment outcomes and safety were evaluated by assessing the general health, function, and behavior of the animals. Joint tissues were analyzed by x‐ray, magnetic resonance imaging, and histopathology. Intra‐articular AMSC therapy was well tolerated in this study. We did not observe adverse systemic reactions, nor did we find evidence of damage to intra‐articular joint tissues. Thus, the data generated in this study show a favorable safety profile for AMSCs within the joint space in support of a phase I clinical trial evaluating the clinical utility of AMSCs to treat osteoarthritis. Stem Cells Translational Medicine 2017;6:910–922